Oral epithelial barrier function and the role of nuclear factor kappa-β pathway in the pathogenesis of aphthous ulceration - Ömer GÜNHAN; Armağan GÜNAL; Arzu AVCI; Şivge KURGAN; Ömür DERECİ; Bülent KURT; Bülent CELASUN (Turkish Journal of Gastroenterology, 2019)
-